Methane Production from Secondary Paper and Pulp Sludge: Effect of Natural Zeolite and Modeling - Huilinir-Curio, C; Montalvo-Martinez, S; Quintriqueo-Cid, A (Elsevier, 2014)
The effect of natural zeolite on methane production from secondary paper and pulp sludge and its modeling are evaluated. Five tests with zeolite concentrations of 0, 0.2, 0.5, 1 and 20g/L were evaluated at 30°C. The modified Gompertz equation, the logistic function and the transfer function were evaluated. The results show that doses between 0.2 and 1g/L of zeolite produce a statistically significant increase of accumulated methane, giving values greater than 183mL for CH4/g of VSadded. On the contrary, the 20g/L dose of zeolite reduced the methane production. The modified Gompertz and the logistic function models concur with the experimental data, the former having the best fit. © 2014 Elsevier B.V.